1970
DOI: 10.3329/bmrcb.v37i1.7793
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of management, control, complications and psychosocial aspects of diabetics in Bangladesh: DiabCare Bangladesh 2008

Abstract: DiabCare Bangladesh 2008 evaluated the current status of diabetes care in Bangladesh as a continuation of similar cross-sectional study conducted previously in 1998. The current study recruited 1952 patients from general hospitals, diabetes clinics and referral clinics to study current scenario of diabetes management from 01 March 2009 to 31 March 2009. We report the results of type 2 diabetic population who constituted 95.3% (n=1860). Results showed deteriorating glycaemic control with mean HbA1c of 8.6±2.0% … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
30
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(36 citation statements)
references
References 11 publications
5
30
0
1
Order By: Relevance
“…It has enrolled relatively higher patients (2092) as compared to previous DiabCare studies. 10, The mean age of the patients (51.3 years) is consistent with previous DiabCare and other studies conducted in Bangladesh. 10,16 The patients in this study had relatively shorter disease duration (6 years) as compared to DiabCare 2008 (7.9 years).…”
Section: Discussionsupporting
confidence: 79%
See 2 more Smart Citations
“…It has enrolled relatively higher patients (2092) as compared to previous DiabCare studies. 10, The mean age of the patients (51.3 years) is consistent with previous DiabCare and other studies conducted in Bangladesh. 10,16 The patients in this study had relatively shorter disease duration (6 years) as compared to DiabCare 2008 (7.9 years).…”
Section: Discussionsupporting
confidence: 79%
“…10, The mean age of the patients (51.3 years) is consistent with previous DiabCare and other studies conducted in Bangladesh. 10,16 The patients in this study had relatively shorter disease duration (6 years) as compared to DiabCare 2008 (7.9 years). Greater proportion of patients with family history of diabetes (61.5% vs. 52.8%) and smoking habits (11.3% vs. 8.2%) has been observed as compared to DiabCare 2008 study.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…10 Here we found that, nephropathy was present in 42.5% of study subjects then retinopathy in 37.8%, neuropathy in 29.8%, CAD in 25.8%, PVD in 14% and stroke in 11%. But previous study from Bangladesh showed microvascular, macrovascular and severe late complications in 39.2%, 9.9% and 12.1% of patients respectively.…”
Section: Discussionmentioning
confidence: 80%
“…But previous study from Bangladesh showed microvascular, macrovascular and severe late complications in 39.2%, 9.9% and 12.1% of patients respectively. 10 It was seen from our study that microvascular complications were common among the study subject who had long duration of diabetes, hypertension, obesity and macrovascular complications were common among the patients with male sex, poor glycemic status, dyslipidemia and family history of DM. There are several study from India, 11 one showed neuropathy was more common (37%) when compared with retinopathy (17%) and nephropathy (20%).…”
Section: Discussionmentioning
confidence: 90%